Human and murine dystrophin mRNA transcripts are differentially expressed during skeletal muscle, heart, and brain development. - Bies, R D (1992)
Dystrophin transcripts were shown to be alternatively spliced in a pattern characteristic of both tissue type and developmental stage. Multiple novel spliced forms of dystrophin mRNA were identified in murine brain tissue, skeletal and cardiac muscle, diaphragm, and human cardiac Purkinje fibers. The transcript diversity was greatest in adult, non-skeletal muscle tissues. Sequence analysis revealed that four tandem exons of the murine gene are differentially spliced in at least 11 separate patterns to generate distinct isoforms. Two of these forms were observed in all tissues examined, while several others were uniquely observed in cardiac muscle and brain. Cardiac Purkinje fibers express an isoform primarily observed in brain tissue. Several spliced transcripts were observed only in postnatal development. Differential utilization of a fifth exon results in two mRNA splice forms that encode separate embryonic and adult C-termini of dystrophin. Comparison of murine with human dystrophin mRNAs showed that similar isoform expression patterns exist across species. These observations suggest that functionally distinct isoforms of the dystrophin protein are expressed in separate tissues and at different stages of development. These isoforms may be of significance in understanding the various tissue-specific effects produced by dystrophin gene mutations in Duchenne and Becker muscular dystrophy patients.